Understanding the relationship between gastronomic experience, satisfaction, and revisit intention - Soonsan, Nimit; Sukhabot, Sasiwemon; Phakdee-Auksorn, Panuwat (Kasetsart Journal of Social Sciences, 2023)
Gastronomic tourism has risen to prominence as a major tourism trend in recent years. The creative city of gastronomy, in particular, now exerts significant influence over tourists’ decisions to visit the destination in search of an extraordinary tourism experience. The purpose of this study was to determine the effect of gastronomic experience on revisit intention and the moderating effect of satisfaction. Through a questionnaire, quantitative data were collected from 525 domestic visitors using convenience sampling. The findings revealed that although the Entertainment — escapism experience had no effect on revisit intention, the Education — esthetics experience did. Additionally, satisfaction was discovered to serve as a perfect mediator between Entertainment — escapist experience and the intention to revisit. Furthermore, it also acted as a partial mediator in the relationship between Education — esthetic experience, and the intention to revisit. Not only do the study’s findings benefit academia by elucidating the effect of prior experiences on future behavior in the context of gastronomic city tourism, but they may also serve as a guideline for destination marketers interested in promoting and developing gastronomic tourism.